SPE Annual Technical Conference and Exhibition 1984
DOI: 10.2118/13249-ms
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Single-Well Pulse Testing of a Three-Layer Stratified Reservoir

Abstract: A new mathematical model is developed for analyzing single-well pulse test data from a reservoir consisting of two permeable zones separated by a less permeable zone. The model considers well-bore storage and skin effects and allows the three zones to have different rock properties. The line-source assumption used in developing the analytic solution is validated via comparison of results with another model also developed in this work. This latter model assumes identical rock properties for the two permeable zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Lee et al [28] proposed the range of 4 at D 5. To obtain desired results, the values of n ¼ 10 4 and at D ¼ 4 are used throughout this study.…”
Section: Solution Of the Governing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al [28] proposed the range of 4 at D 5. To obtain desired results, the values of n ¼ 10 4 and at D ¼ 4 are used throughout this study.…”
Section: Solution Of the Governing Equationmentioning
confidence: 99%
“…It is required to optimize the parameters α and n for improving the accuracy. Lee et al proposed the range of 4 ≤ αt D ≤ 5. To obtain desired results, the values of n = 10 4 and αt D = 4 are used throughout this study.…”
Section: Theoretical Modellingmentioning
confidence: 99%
“…Moreover, from Lee et al, 42 the values of apτ lies between 4 and 5. So, Equation (28) converges more quickly due to the noninclusion of oscillating sine and cosine functions where the optimal value is: apτ=4.7ap=4.7τ.…”
Section: Present Solution: Integral Transform Methodsmentioning
confidence: 82%
“…Lee et al [50] suggested values of a p τ ranging between 4 and 5. Equations (41)- (43) and (45) converge more quickly because it does not contain oscillating cosine and sine functions.…”
Section: Case 1 Linear Variation Of Thermal Conductivity With the Fimentioning
confidence: 99%